Anti-Obesity Actions of Two Separated Aqueous Extracts From Arbutus () and Hawthorn () Fruits Against High-Fat Diet in Rats via Potent Antioxidant Target - Soumaya Wahabi; Kais Rtibi; Amal Atouani; Hichem Sebai (SAGE Publishing, 2023)
Arbutus unedo and Crataegus monogyna are widely distributed throughout the Mediterranean basin and commonly used in folk medicine against a wide range of diseases. Therefore, the present study has been designed to evaluate the anti-obesity potential of two aqueous extracts of the fruits of A. unedo (AUAE) and C. monogyna (CMAE). Male Wistar rats were supplied with a standard diet (SD), high-fat diet (HFD), HFD with the two separated extracts at the same dose (300 mg/kg, BW, p. o.), or HFD with atorvastatin-(ATOR) (2.1 mg/kg, BW, p. o.) for 12 weeks. Lipid profile and the liver and kidney linked-markers were assessed. Besides, obesity-related disorders' biomarkers were measured. AUAE, CMAE, and ATOR were observed to reduce significantly total body and organ weights following HFD-induced obese rat models. Likewise, epididymal and abdominal adipose tissue weights were noticeably decreased in HFD rats treated with both extracts and ATOR. Added to that, biochemical and metabolic changes were normalized by significant attenuation of lipid peroxidation accompanied with an increase of thiol-group concentrations and antioxidant status. More importantly, a modulation in trace element levels was revealed when compared with HFD group. Altogether, current study concluded that AUAE and CMAE could be potential candidates for the prevention and treatment of obesity and related disturbs induced by HFD.